Correction: Sustainable bioproduction of the blue pigment indigoidine: Expanding the range of heterologous products in R. toruloides to include non-ribosomal peptides. Issue 21 (21st October 2019) - Wehrs, Maren; Gladden, John M.; Liu, Yuzhong; Platz, Lukas; Prahl, Jan-Philip; Moon, Jadie; Papa, Gabriella; Sundstrom, Eric; Geiselman, Gina M.; Tanjore, Deepti; Keasling, Jay D.; Pray, Todd R.; et al.
Abstract : Correction for 'Sustainable bioproduction of the blue pigment indigoidine: Expanding the range of heterologous products in R. toruloides to include non-ribosomal peptides' by Maren Wehrs et al., Green Chem., 2019, 21, 3394–3406.